Parametric design for sustainable marine infrastructure - Abdolpour, Hassan; Marut, Maciej (Bulletin of the Polish Academy of Sciences Technical Sciences, 2025)
As coastal cities expand and confront the challenges posed by climate change, the imperative for sustainable infrastructure is becoming increasingly urgent. Marine infrastructure such as ports, quays, and ferry terminals are vital to urban ecosystems; however, they significantly impact the environment due to substantial material consumption and high energy requirements. Innovative solutions are essential to enhance design efficiency, reduce carbon emissions, and ensure long-term durability. Digital methodologies, including parametric design, building information modeling (BIM) and remote monitoring, present promising avenues toward sustainable marine infrastructure. By leveraging intelligent design processes and real-time data integration, these approaches can minimize material waste, extend structural lifespan, and promote eco-friendly urban development. This paper explores how the integration of these digital tools can contribute to the advancement of sustainable urban systems, aligning with contemporary development trends in urban infrastructure.